Human anxieties, bovine solutions: Political subtexts of native cattle conservation in north-eastern Siberia - Tarasova, Zoia (University of Cambridge, 2020)
For over 300 years the Turkic-speaking Sakha of north-eastern Siberia have lived uneasily in a colonial relationship with the Russian/Soviet state. Since the 1990s, there has been a strong ethnic de-colonising backlash which has struggled to find an appropriate form, from attempts to revive shamanism to budgetary wrangles with the federal government in Moscow. The economy and identity of the Sakha people are closely bound up with cattle. I argue that cattle are now coming to be used as a metaphor for the Sakha people themselves, to create a new and powerful ethnonationalist discourse. This focuses on a distinctive local breed, which under Soviet technocratic agriculture was considered primitive, hybridised with Russian breeds, and made almost extinct –¬ just as, it is now claimed, Soviet social evolutionist policies encouraged Sakha humans to catch up with and assimilate with Russians. I analyse this as a series of parallel anxieties: not simply about the racial purity of the Sakha people, but also about the virility of Sakha men, the chastity of Sakha women when tempted by Russian and now Muslim migrant men, and their right to political self-determination within the larger Russian state. I argue that all this is displaced and projected onto the endangered breed of local cattle. By raising the native cattle in isolation from other breeds, castrating non-Sakha bulls and selectively mating native females with native males, Sakha nationalists are compensating for aspirations which they cannot realise in the human realm. I trace the connections between all the participants in this process by conducting long-term fieldwork in three sites. I start with the urban intellectuals in Yakutsk city who have no direct experience of farming but drive this movement. I then move on to two contrasting villages where rural herders are induced to slaughter their modern hybridised cattle and revert to keeping this archaic breed. One is a Sakha village near the city which has been turned into a cattle conservation farm, the other an ...